SMART APPS CREATOR TO ENHANCE STUDENTS’ SPEAKING ABILITY: A CLASSROOM ACTION RESEARCH - Astuti, Yulia Fitri; Rokhayani, Atik; Kurniati, Diah (SIMPLE: International Journal of English Education, 2024)
Teaching English in Indonesia Junior High School faces challenges, such as low speaking ability among students. Only 31% complete initial assessments, while 69% are below KKM. To address this, interactive learning media like Smart Application Creator (SAC) can be used to create applications and IOS without programming code. The purpose of this research was to overcome the problems experienced by almost all students in learning speaking skills, such as lack of self-confidence, limited vocabulary, or often mispronunciation of words using the Smart Application Creator (SAC) media. Subjects in this study were the students of class VII-B from SMP N 1 Trangkil. The researcher used the Classroom Action Research method to see how the using of SAC can increase students' speaking skills. There are three instruments used in this study to collect the data, namely; Observation sheet, Interview, and Test. The analysis and discussion in chapter IV show that using Smart Application Creator (SAC) media for Speaking Self Introduction in class VII B SMP N 1 Trangkil improves students' attitude and learning outcomes. The average learning attitude increased from 71.55 in cycle I to 88 in cycle II, with 66.7% of students achieving good attitudes and -66.7% not. The average learning outcomes increased from cycle I to cycle II, with 56.25% of students achieving completeness and 31.25% achieving not. The results suggest that using SAC media can improve students' Speaking Self Introduction outcomes in the 2022/23 academic year.